2019
DOI: 10.1111/evo.13664
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of maternal effects to dietary selection in Mediterranean fruit flies

Abstract: Individual responses to dietary variation represent a fundamental component of fitness, and nutritional adaptation can occur over just a few generations. Maternal effects can show marked proximate responses to nutrition, but whether they contribute to longer term dietary adaptation is unclear. Here, we tested the hypotheses that maternal effects: (i) contribute to dietary adaptation, (ii) diminish when dietary conditions are constant between generations, (iii) are trait‐specific and (iv) interact with high‐ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…First, the environment must be heterogeneous. In a stable environment, parental environmental cues are uninformative and the influence of parental environmental can evolve to slightly negative values (Klironomos et al 2013, Kuijper and Hoyle 2015, Leftwich et al 2019). Second, the environmental heterogeneity must be within an intermediate frequency and without repeated extreme events, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…First, the environment must be heterogeneous. In a stable environment, parental environmental cues are uninformative and the influence of parental environmental can evolve to slightly negative values (Klironomos et al 2013, Kuijper and Hoyle 2015, Leftwich et al 2019). Second, the environmental heterogeneity must be within an intermediate frequency and without repeated extreme events, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal effects during development tend to occur under both favorable and stressful conditions (Rösvik et al, 2020), which may facilitate adaptation to novel environments (Fox & Savalli, 1998; Leftwich et al, 2019) or buffer against changing conditions through transgenerational phenotypic plasticity (Shama et al, 2014). We found that maternal effects, besides being influenced by the offspring’s developmental stage, can also depend on other factors such as the offspring environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of the Mediterranean fruit fly have shown that adult protein-rich diets enhance male sexual performance attributes such as sexual signaling [ 50 , 51 , 52 ], participation in leks, mating success and duration, and inhibition of female remating [ 34 , 53 , 54 , 55 , 56 , 57 , 58 ]. In addition to the effect of adult diets, there are also studies that demonstrate the determinant effect of larval diet content on both male sexual performance [ 59 ] and other insect fitness traits [ 60 , 61 ], and the nutritional adaptation that occurs during long-term laboratory rearing that leads to significant variation across different fitness-related traits [ 59 , 61 ]. Another critical factor that affects sexual calling behavior is the age of the males.…”
Section: Introductionmentioning
confidence: 99%